Environmental spray simulation: Reproductive effects of glyphosate in an animal model - Simões, Jamile Silveira Tomiazzi; Bastianini, Mariana Esperendi; Uzelotto, Mariany Kerriany Gonçalves; Rossi, Renata Calciolari; Favareto, Ana Paula Alves (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The aim of the present study was to evaluate the reproductive effects caused by chronic inhalational exposure to glyphosate in animals. For this, a model that simulates real environmental spraying with environmentally relevant concentrations of glyphosate was used. Wistar rats were divided into 4 groups, exposed to 0 (control group - GC), 20.69 (low concentration group - LCG), 34.63 (medium concentration group - MCG) or 51.66 ppm/day (group of high concentration - HCG). The animals were exposed for 15 minutes for 180 days. After the exposure period, the animals were euthanized and the testes and epididymis were collected for analysis of sperm counts, motility, morphology and vitality. The absolute and relative numbers of spermatozoa in the testis and epididymis and daily sperm production were reduced in all groups exposed to the herbicide, indicating an impact on spermatogenesis. Progressive motility was reduced in GAC, with a consequent increase in non-progressive motility and immobility. However, there was no delay in sperm transit time in the epididymis. Plasma membrane integrity and the percentage of morphologically normal spermatozoa were reduced in the exposed groups, with an increase in head and tail abnormalities. Exposure to glyphosate through an environmental spray simulation model affected sperm quantity and quality in an animal model. This warns of risks to male fertility, demanding strict regulation on the use of pesticides to prevent damage to reproductive health and the environment. In this way, more sustainable agricultural measures are crucial to balance production and global health.
Keywords: Herbicide; Reproduction; Environmental health